Pemuda dan Pertanian: Kajian Minat dalam Kegiatan On-Farm dan Off-Farm di Kabupaten Purbalingga - Hernowo, Hernowo; Aprilliani, Fenny; Cahyaningtyas, Nur Indah; Rahmawati, Sofia; Sidiq, Muhamad Fajar (Universitas Galuh, 2025)
The era of agricultural modernization in the 4.0 industrial revolution is often expected to change old habits in on-farm and off-farm agriculture. Modernization of agriculture can be a new hope and a great opportunity for farmers, especially young people. From this great opportunity, it is able to estimate and minimize the risk of losses from agricultural crops due to yield loss. This study aims to assess youth interest in on-farm and off-farm activities in the agricultural sector in Purbalingga Regency. In this study, a survey method was used to collect primary research data. The research data were collected by observation, literature study, interviews, and questionnaires. The sampling technique was carried out using quota sampling. The number of respondent samples taken as the object of research was 120 youth. The results of the analysis show that youth have a high interest in on-farm and off-farm activities. The highest average score on the implementation indicator in off-farm activities (3.356) and the lowest average score on the planning indicator in on-farm activities (2.650).